2018
DOI: 10.31234/osf.io/mc9jv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RZ Interval as an Impedance Cardiography Indicator of Effort-Related Cardiac Sympathetic Activity

Abstract: Research on effort and motivation commonly measures how the sympathetic branch of the autonomic nervous system affects the cardiovascular system. The cardiac pre-ejection period (PEP), assessed via impedance cardiography, is a common sympathetic outcome, but assessing PEP requires identifying subtle points on cardiac waveforms. The present research examined the value of the RZ interval (RZ), which has recently been proposed as a measure of sympathetic activity, for effort research. Also known as the initial sy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The pattern, shown in Table 1, essentially paralleled the pattern for PEP. As an aside, the model R 2 was slightly higher for RZ (11.9%) than for PEP (10.6%), which replicates the larger effect sizes found for RZ found in recent experiments using incentives (Silvia et al, 2016) and other effort paradigms (Silvia, Beaty et al, 2014; Silvia, Nusbaum et al, 2014). …”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The pattern, shown in Table 1, essentially paralleled the pattern for PEP. As an aside, the model R 2 was slightly higher for RZ (11.9%) than for PEP (10.6%), which replicates the larger effect sizes found for RZ found in recent experiments using incentives (Silvia et al, 2016) and other effort paradigms (Silvia, Beaty et al, 2014; Silvia, Nusbaum et al, 2014). …”
Section: Resultssupporting
confidence: 83%
“…Also known as the initial systolic time interval (ISTI; Meijer, Boesveldt, Elbertse, & Berendse, 2008), RZ is increasingly popular as a measure of contractility. Several effort studies have found that it works at least as well as PEP (Silvia, Beaty, Nusbaum, Eddington, & Kwapil, 2014; Silvia, Nusbaum et al, 2014; Silvia et al, 2016), possibly because it uses the salient R and Z points instead of the subtle Q and B points (van Lien, Schutte, Meijer, & de Geus, 2013). PEP and RZ were assessed by ensemble averaging (Kelsey et al, 1998) the ECG and dZ/dt waveforms within each 60 second period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…See the online supplemental materials for information on the RZ interval, a similar cardiac outcome(Silvia, McHone, et al, 2018).…”
mentioning
confidence: 99%